A Vivaldi Antenna with Improved Bandwidth and Gain - Elhefnawy, Mohamed; Podd, Frank (International Journal of Electrical and Computer Engineering Systems, 2022)
In this paper, the radiation characteristics of the conventional Vivaldi antenna are improved by proposing a novel design of a Vivaldi antenna. This proposed Vivaldi antenna is excited through three slots by using the L-probe microstrip feeder. The novel design can provide higher gain and wider bandwidth compared to that of the conventional Vivaldi antenna of the same size. The CST MWS software is used to simulate the proposed Vivaldi antenna. The measured and the simulated S-parameters were compared so that the feasibility of the proposed Vivaldi antenna was validated. The measured S-parameters show that the impedance bandwidth of the proposed Vivaldi antenna was from 1.976 to 7.728 GHz, while the measured maximum gain is 4.9 dBi at the operating frequency of 3 GHz.